Screening of Selected Chemotherapeutant by using Primary Liver cell Culture of Labeo rohita (Hamilton, 1822) - Choudhary, Pushpa; Tripathy, Gayatri; Pani Prasad, K. (Fishery Technology, 2019)
Development of primary cell culture from liver tissues of Labeo rohita was successfully completed by following explant culture method. The L-15 media supplemented with 20% foetal bovine serum (FBS) at 28oC has resulted in good attachment and proliferation of primary culture. FBS is required for efficient attachment of liver explant but increased supplementation of FBS in media did not stimulate the proliferation of cells. Radiation from liver explant was first seen after 48 h of attached explant. The monolayer formation of liver cell culture was observed after twenty one days and it was subsequently sub cultured for more than 10 times. The in vitro cytotoxicity of a commonly used drugs (Oxytetracycline), chemotherapeutant (Benzalkonium chloride) and insecticide (Fipronil) was studied on primary liver cell culture of L. rohita by assessing cell viability using tetrazolium (MTT) assay which revealed that Fipronil is most toxic compared to OTC and BKC. Reduction in cell viability was observed with the increase in concentration of chemotherapeutants. The IC50 values of OTC, BKC and Fipronil calculated from dose-response curve were 76.43 Î¼g ml-1, 3.22 Î¼g ml-1 and 0.014 Î¼g ml-1 respectively. The study revealed that primary cell culture from liver tissue of L. rohita can be used as a potentially bio-indicator for the in vitro screening of the acute toxicities of Fipronil.